Future bioenergy source by microalgae-bacteria consortia: a circular economy approach - Chia S.R.; Ling J.; Chia W.Y.; Nomanbhay S.; Kurniawan T.A.; Chew K.W. (Royal Society of Chemistry, 2024)
The potentiality of microalgae-bacteria consortia applied in a circular economy is acknowledged and explored